Effect of collection methods on combustion particle physicochemical properties and their biological response in a human macrophage-like cell line. Issue 12 (15th October 2019) - Kaur, Kamaljeet; Jaramillo, Isabel C.; Mohammadpour, Raziye; Sturrock, Anne; Ghandehari, Hamidreza; Reilly, Christopher; Paine, Robert; Kelly, Kerry E.
Abstract: In vitro studies are a first step toward understanding the biological effects of combustion-derived particulate matter (cdPM). A vast majority of studies expose cells to cdPM suspensions, which requires a method to collect cdPM and suspend it in an aqueous media. The consequences of different particle collection methods on particle physiochemical properties and resulting biological responses are not fully understood. This study investigated the effect of two common approaches (collection on a filter and a cold plate) and one relatively new (direct bubbling in DI water) approach to particle collection. The three approaches yielded cdPM with differences in particle size distribution, surface area, composition, and oxidative potential. The directly bubbled sample retained the smallest sized particles and the bimodal distribution observed in the gas-phase. The bubbled sample contained ∼50% of its mass as dissolved species and lower molecular weight compounds, not found in the other two samples. These differences in the cdPM properties affected the biological responses in THP-1 cells. The bubbled sample showed greater oxidative potential and cellular reactive oxygen species. The scraped sample induced the greatest TNFα secretion. These findings have implications for in vitro studies of air pollution and for efforts to better understand the underlying mechanisms.